Abrasion, Pilling, and Snagging Properties of Half-bleached Bedsheet Fabrics Made from 100% Cotton Yarns with Various Parameters - Desalegn Atalie; Gashaw Ashagre (Journal of Natural Fibers, 2022)
The bedsheet is one of the most common direct contact textile products in our daily life and it may cause discomfort during sleeping due to several factors. In this study, the effect of yarn parameters on abrasion, pilling, and snagging resistance of half-bleached bedsheet fabric has been investigated. Nine woven bedsheet fabrics were manufactured from the same warp yarn count (20Tex) and three types of weft yarn counts (21.5, 25, and 30Tex) with three incremental yarn twists for each type of yarn count. The bedsheet fabrics underwent half-bleach treatment before property evaluation. The results show that the bedsheet fabric made from coarser yarn count (30Tex) and the least twist (826 TPM) have very good abrasion resistance of 96%–97.86% (least mass loss 2.15%–3.95%) than others. The statistical analysis proves that the pilling and snagging properties of bedsheet fabrics are affected by yarn count and twist. However, abrasion resistance in the appearance change method is insignificant at an F-value of 12.761 and P-value of 0.058. Linear regression results show that yarn count (Tex) and abrasion resistance (mass loss method) has a positive correlation at Adj.R2 value of 86.5%. Yarn twist also has a positive correlation with abrasion mass loss ratio and snagging resistance at Adj.R2 values of 97.4% and 87%, respectively.